Latino Adolescents’ Daily Bicultural Stress and Sleep: Gender and School Context Moderation - Sladek, Michael R. (Health Psychol, 2019)
OBJECTIVE: Bicultural stress (i.e., challenge arising from navigating two cultural contexts) has significant consequences for Latino youth’s health, but researchers have yet to examine the implications of bicultural stress for adolescents’ sleep. The goals of this study were to examine whether individual and day-to-day (within-person) differences in bicultural stress were associated with Latino adolescents’ sleep onset latency (i.e., time to fall asleep), sleep midpoint (i.e., sleep schedule), sleep duration (i.e., time asleep), and subjective sleep quality. METHODS: Participants were 209 Latino late adolescents (M(age) = 18.10; 64.4% female) attending over 90 different high schools who completed seven daily diary surveys while wearing actigraph wristwatches (N = 1,320 daily observations). Participants also reported sleep problems in a standard survey. Statistical interactions were tested to assess moderation by gender and co-ethnic school composition. RESULTS: On average, more bicultural stressors across the week were associated with lower average sleep duration and more sleep problems for males (compared to females) and youth attending schools with higher (compared to lower) Latino student enrollment. Regarding day-to-day differences, more daily bicultural stressors than usual predicted longer sleep onset latency that night for males, earlier sleep midpoint that night, and less sleep duration that night for youth attending higher Latino-enrollment schools. CONCLUSIONS: Latino adolescents’ everyday experiences of bicultural stress relate to differences in sleep duration, timing, and quality, with important variation by gender and school context. Results advance existing theory regarding social position factors that differentiate the health implications of bicultural stress for Latino youth.